Meningeal Irritation : A Review - Hassan, AM Shafiqul; Ekram, ARM Saifuddin; Rahman, Syed Wahidur; Ashar, MA; Muhammad, Quazi Deen (TAJ: Journal of Teachers Association, 2009)
Cases of meningeal irritation are prevalent worldwide and much Infectious and non-infectious aetiology exist for this condition. Sub-arachnoid haemorrhage (SAH), central nervous system sarcoidosis(neuro-sarcoidosis) . systemic lupus erythematosus (SLE), drugs and chemicals are the non-infectious causes of meningeal irritation. But much is focused on infectious causes because infection of the central nervous system (CMS) is a medical emergency. The clinical constellation of fever, headache and neck-stiffness is diagnostic of meningitis. Other clinical findings like Kernig's sign, Brudzinski's sign and extensor plantar responses support the diagnosis of meningitis and / or meningo-encephalitis. The clinical onset of sudden severe headache, vomiting and unconsciousness is diagnostic of SAH. Neck rigidity, positive Kernig's sign and sub-hyaloid haemorrhage on fundoscopic examination support the diagnosis. However, diagnosis of meningitis and its treatment is very much important and critical in particular. A patient presenting with fever and unconsciousness with no substantial pre-existing illness eg. HTN, DM, endocrinopathy and.' or history of traveling from a malarial epidemic area should be differentially considered meningo-encephalitis for once at least. doi: 10.3329/taj.v15i2.3922 TAJ December 2002; Vol.15(2): 108-114